Recreational cannabis use impairs driving performance in the absence of acute intoxication. (1st March 2020) - Dahlgren, M. Kathryn; Sagar, Kelly A.; Smith, Rosemary T.; Lambros, Ashley M.; Kuppe, Madeline K.; Gruber, Staci A.
Highlights: Cannabis users had poorer driving simulator performance relative to controls. Users were not intoxicated during testing suggesting residual effects of use. Impairment was primarily localized to early onset (before age 16) cannabis users. Earlier age of onset of cannabis use was associated with more severe impairment. Covariate analyses indicate that impulsivity influences performance differences. Abstract: Background: Across the nation, growing numbers of individuals are exploring the use of cannabis for medical or recreational purposes, and the proportion of cannabis-positive drivers involved in fatal crashes increased from 8 percent in 2013 to 17 percent in 2014, raising concerns about the impact of cannabis use on driving. Previous studies have demonstrated that cannabis use is associated with impaired driving performance, but thus far, research has primarily focused on the effects of acute intoxication. Methods: The current study assessed the potential impact of cannabis use on driving performance using a customized driving simulator in non-intoxicated, heavy, recreational cannabis users and healthy controls (HCs) without a history of cannabis use. Results: Overall, cannabis users demonstrated impaired driving relative to HC participants with increased accidents, speed, and lateral movement, and reduced rule-following. Interestingly, however, when cannabis users were divided into groups based on age of onset of regular cannabis use, significant driving impairment was detected and completely localized to those with early onset (onset before age 16) relative to the late onset group (onset ≥16 years old). Further, covariate analyses suggest that impulsivity had a significant impact on performance differences. Conclusions: Chronic, heavy, recreational cannabis use was associated with worse driving performance in non-intoxicated drivers, and earlier onset of use was associated with greater impairment. These results may be related to other factors associated with early exposure such as increased impulsivity.